Entering Research: A Course That Creates Community and Structure for Beginning Undergraduate Researchers in the STEM Disciplines - Balster, Nicholas (American Society for Cell Biology, 2010)
Undergraduate research experiences have been shown to enhance the educational experience and retention of college students, especially those from underrepresented populations. However, many challenges still exist relative to building community among students navigating large institutions. We developed a novel course called Entering Research that creates a learning community to support beginning undergraduate researchers and is designed to parallel the Entering Mentoring course for graduate students, postdocs, and faculty serving as mentors of undergraduate researchers. The course serves as a model that can be easily adapted for use across the science, technology, engineering, and mathematics (STEM) disciplines using a readily available facilitator's manual. Course evaluations and rigorous assessment show that the Entering Research course helps students in many ways, including finding a mentor, understanding their place in a research community, and connecting their research to their course work in the biological and physical sciences. Students in the course reported statistically significant gains in their skills, knowledge, and confidence as researchers compared with a control group of students, who also were engaged in undergraduate research but not enrolled in this course. In addition, the faculty and staff members who served as facilitators of the Entering Research course described their experience as rewarding and one they would recommend to their colleagues.